Layman's guide to psychiatry and psychoanalysis - "Berne, Eric" (Bombay, 1969)
A book emphasized on the subject of psychoanalysis/psychiatry, or the clinical method for treating psychopathology through dialogue between a patient and a psychoanalyst, his impact on the field of psychology cannot be overstated.
Keywords: Psychiatry